DIGITALISASI KEKERASAN PEREMPUAN : STUDI REPRODUKSI PELECEHAN MELALUI MEDIA SOSIAL - Islami, Prima (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2021)
The process of digitalization is due to the development of communication and technology information to create new media include content and also a change of media communication. Changes in all the media have an impact on significant changes. Social media are a new form of mass media that constructs the identity of the roles by men or women. Digitizing violence against women through media reproduces harassment through social media. This study was made to answer some questions about reproduction of harassment in social media, the pattern of constructing online gender-based violence by media communication, the impact of the social media on the victim and the last about the government policies view to transform violence against women in the digital space. This study uses a qualitative approach with discourse analysis of the content and comment on the three main social media. There a three main of social media that are used by the public. This study also uses the social network analysis method to study digital communication patterns in social media. The social network analysis is used to know issues that are used by the media. The result of this study is social media build a new form of harassment by media that places women as an object due to the domination of power built by patriarchal culture. Harassment by media due to women has an impact on other types of harassment as malicious comments, hate speech, indecent image as content, and online harassment. These conditions impact to the emergence of gender inequality such as marginalization, subordination of women due to built stereotypes, and a double burden on women as victims of violence reproductive in social media.